Assessment of the tsunami‐induced current hazard. Issue 6 (18th March 2014) - Lynett, Patrick J.; Borrero, Jose; Son, Sangyoung; Wilson, Rick; Miller, Kevin
Abstract The occurrence of tsunami damage is not limited to events causing coastal inundation. Even without flooding, maritime assets are vulnerable to significant damage from strong currents and associated drag forces. While such impacts have been observed in the past, they have not been well studied in any context. Nearshore tsunami currents are governed by nonlinear and turbulent physics and often have large spatial and temporal variability making high‐fidelity modeling particularly challenging. Furthermore, measured data for the validation of numerical simulations is limited, with few quality data sets appearing after recent tsunami events. In this paper, we present a systematic approach for the interpretation of measured tsunami‐induced current impacts as well as a validation approach for simulation tools. The methods and results provided here lay the foundation for much needed efforts to assess tsunami hazards in ports and harbors.